The Effect of the Covid-19 Pandemic on the Crime of Theft - Syamsuddin, Rahman; Fuady, Muhammad Ikram Nur; Prasetya, Muh. Djaelani; M, Andi Anas Chaerul; Umar, Kusnadi (International Journal of Criminology and Sociology, 2021)
This research aims to assist the police institution in preventing theft crimes that increased during the Covid-19 period by mapping areas prone to theft crimes based on the incident's location and the level of intensity of theft crimes. This research is empirical, managed quantitatively by collecting data through documentation and literature study. The results showed an increase in the number of theft crimes by 42.65% in Makassar City during the six months of the coronavirus pandemic period. This research also succeeded in mapping the locations prone to theft crimes, mostly in residents' homes rather than in the business center, the central area of money circulation. The research results also show that almost all sub-districts in Makassar City are the places where theft crimes occur, dominated by medium and high categories symbolized by red, yellow, and green color. This study recommends that police institutions pay more attention to residential areas, which are the areas where theft crimes most occur during the pandemic period. Furthermore, this research implies that it can become a reference for the police institution to prepare efforts to prevent theft crimes in Makassar City and other areas during the Covid-19 period.